Too many women? : - Guttentag, Marcia (Sage Publications, 1983)
The basic premise of this provocative book is a startling one - that sex ratios among people on the marriage market have profound consequences for a wide variety of attitudes, values, and behaviors, from sexual mores and behavior to shifts in economic power...the authors share with the reader a wealth of fascinating data and information...a book which is...fascinating, scholarly, provocative and exceedingly well-written.